Advertisement call and morphological variation of the poorly known and endemic Bokermannohyla juiju Faivovich, Lugli, Lourenco and Haddad, 2009 (Anura: Hylidae) from Central Bahia, Brazil - Taucce, Pedro P. G. [UNESP]; Pinheiro, Paulo D. P. [UNESP]; Leite, Felipe S. F.; Garcia, Paulo C. A. (Magnolia Press, 2015)
Bokermannohyla juiju is a member of the B. martinsi species group and it was described based on one male specimen. In order to enhance the knowledge about the species, we describe its advertisement call and morphological variation, including for the first time data on females. We also provide additional comments about its natural history, geographic distribution, and conservation. The advertisement call of B. juiju consists of a single note, non-pulsed, harmonic structured call emitted several times in a row. Four out of five males were found calling in bromeliads. The female, as it is common in many Bokermannohyla species, presents some morphological features not shared with the males, like a non-hypertrophied forearm and less developed prepollex.
Keywords: Amphibia; Bioacoustics; Cophomantini; Hylinae; Taxonomy; Espinhaco Range